The Role of Self-Efficacy in Higher Education Students for Human Resource Development: A Systematic Literature Review - Dinis Cahyaningrum; Tifani Dame Hasany; Khairul Mujahidi; Ni Wayan Adelia Mutiara Asri (North Press, 2026)
Academic self-efficacy is an important factor that influences students’ academic success, persistence, and professional competency development in higher education. However, previous studies have mainly focused on academic achievement and motivation, while limited studies have discussed its contribution to human resource development using the integration of Social Cognitive Theory (SCT) and Social Cognitive Career Theory (SCCT). Therefore, this study aims to analyze the role of academic self-efficacy in supporting academic achievement, student persistence, and human resource development among higher education students. This study used a descriptive qualitative approach through a literature review by analyzing previous studies from books, journal articles, and academic publications. The data were analyzed using thematic analysis to identify major themes and relationships among previous findings. The results showed that academic self-efficacy positively influences motivation, learning engagement, academic persistence, career readiness, adaptability, and employability skills. The novelty of this study lies in integrating SCT, SCCT, and Human Resource Development (HRD) perspectives to explain the broader role of academic self-efficacy in preparing adaptive and competitive human resources in higher education.